Effectual Decision Making and Networks in the Internationalization Process of a Non-Profit Organization - Case of Slush - Lintilä, Katja (My University, 2018)
Today, many organizations are expanding abroad from domestic markets. Despite internationalization literature focuses mainly on for-profit companies, there have been signs of the remarkable expansion of non-profit sector during the last decades. Hence, these types of organizations cannot be neglected. This Master’s thesis focuses on the effectual decision making and networks in the internationalization process of a non profit organization. The aim is to examine, firstly, how non-profit organizations make effectual decisions during the internationalization process and secondly, how networks influence this decision making. The latest version of Uppsala model by Vahlne and Johanson (2017), the effectuation theory by Sarasvathy (2001) and the network approach of internationalization by Johanson and Mattson (1987) are applied as the theoretical tools in this study. For this qualitative and explorative study, the empirical evidence was collected from six representatives of a non-profit organization Slush through semi-structured interviews. Also, secondary data of Slush Tokyo was used besides the primary data of Slush China and Slush Singapore in order to include perspectives from all three Asian locations that Slush has expanded. The findings suggest that effectuation logic is extensively used besides causation logic in the decision making; and it can lead in successful internationalization of a NPO. As the effectuation logic relies on human agency, networks are viewed as the key resource for a NPO. Especially, the key informants have a remarkable role in the early phases of the internationalization. Also, due to the NPOs’ general mission to make a societal change, the accountability for key stakeholders is considered as an important motivator for a NPO’s internationalization. As a result, this study proposes three propositions of using networks in the effectual decision making in the internationalization process of a NPO.
Keywords: Internationalization process; non-profit organization; decision making; effectuation theory; networks; fi=Master's Degree Programme in International Business|